On the effects of orthotropic materials in flutter protection of wind turbine flexible blades. Issue 227 (August 2022) - Torregrosa, A.J.; Gil, A.; Quintero, P.; Cremades, A.
Abstract: Decarbonization requirements have extended the use of wind turbines by orders of magnitude. Due to their high stiffness-to-weight ratio, composite materials have been widely used for manufacturing the turbine blades in the recent years. As a consequence of the orthotropic mechanical properties of these materials, the structural behavior of the blade is conditioned by the orientation of the fibers. This article gives a general idea of the benefits of optimizing the composite material ply angle. Along the paper, two different structures are analyzed, a quasi-isotropic material and a structure with oblique fibers. The analysis is conducted using a reduced order model solver which couples a beam element structural solver with the blade element momentum and Theodorsen pitching airfoil theories. The solvers are validated, and then, the flutter conditions are obtained and used to limit the whole operation curve for both blades. The oblique layup structure is evidenced to increase the critical wind velocity by 10% for a defined control law and electrical system. Therefore, the importance of a correct structural analysis is demonstrated to be crucial in the design and manufacturing of the following generation of wind turbine blades. Highlights: A reduced order model for the aeroelastic calculation of orthotropic thin-walled section wind turbine blades is presented. The structural and aerodynamic models have been validated using high order simulations and experimental data. Flutter wind velocity has been calculated for a quasi-isotropic and oblique fibers layup. For aeroelastic stable conditions the influence of the nondimensional stiffness on the power coefficient is negligible. Oblique fiber structure increases the flutter wind velocity by 10%.